Retroperitoneoscopic single-instrument horseshoe nephrectomy for dilated non-functioning right moiety. Issue 4 (August 2021) - Chong, Clara; Mishra, Pankaj; Paul, Anu; Taghizadeh, Arash; Garriboli, Massimo
Summary: Retroperitoneoscopic horseshoe nephrectomy is an uncommon procedure, in particular in the paediatric practice. We present a procedure carried out via a posterior approach with a single working port in a 20 months old boy. The video goes through the technical aspect, from the positioning of the patient and the port insertion, to the end of procedure. Highlighted are the critical steps of directing the initial fascial dissection more caudal and medial compared to a standard approach for nephrectomy, as well as tips to safely ligate and divide the very short right renal vein. The operative time was 90 min. The postoperative course was uneventful. The retroperitoneal access provides a good visualisation of the hylum (including the IVC in case of right side approach), the ureter and the isthmus and has the advantage to preserve the abdominal cavity. The retroperitoneal approach is safe also in horseshoe kidney.